Ekspresi dosa-dosa besar dalam al-quran dan hadith: satu penelitian terhadap isu-isu di era digitalisasi - Mohamad, Hasbullah; Ayub, Mohd Nasir; Hasan, Surita Hartini (Journal of Islamic, Social, Economics and Development (JISED), 2025)
The era of digitalization has profoundly transformed the social, cultural, and communicative landscapes of contemporary societies. This study examines the concept of major sins (al-kabā’ir) as articulated in the Quran and hadith, and explores how their manifestations provide clear moral lessons that demand serious attention and appropriate responses. The main objective of this study is to understand how the revelatory approach, through its expressions concerning major sins, has a profound impact on the reality of moral and human value degradation, particularly in today’s digital era. Methodologically, the study employs a qualitative textual analysis of Quranic verses and Prophetic traditions related to major sins, complemented by case studies of digital social phenomena such as shirk and superstitions, slander, online fraud, and related issues. The findings indicate that although the outward forms of sinful acts have undergone transformation through digital platforms, the underlying principles and values being transgressed remain firmly embedded within the framework of major sins delineated by Islamic law. The research underscores the pivotal role of religious scholars, Islamic educators, and faith-based institutions in addressing these new challenges through approaches that are both technologically responsive and theologically grounded. It also proposes strategies for addressing modern manifestations of sin, ensuring that the transmission of religious teachings remains rooted in divine revelation while remaining relevant to contemporary challenges. In conclusion, the Quran and hadith not only retain their enduring relevance as sources of ethics and guidance, but also demonstrate adaptive capacity in confronting the diverse forms of moral transgressions arising from digital developments. This study further opens avenues for critical dialogue on reconceptualizing the impact of sin within the digital framework and the urgent need for the development of a robust and progressive digital fiqh.